Assessing intercultural competence (IC) of state junior high school English teachers in Yogyakarta - Idris, Mas Muhammad (Indonesian Journal of Applied Linguistics, 2020)
Intercultural competence (IC) is a concept whichthat has gained importance in recent years. It seems to be transparent, accepted as well as used both in formal and informal situations. This concept can be defined as an individual’s capability to communicate effectively and appropriately with other people who have different cultures, norms, and values. In order for a person to be labeled as an intercultural speaker with intercultural competence, s/he should have the competence of intercultural attitude, skill, and knowledge. However, this competence has not been noticed and assessed comprehensively inside and outside academia, particularly in the setting of English language teaching. Hence, this study aims to assess and determine the level of intercultural competence of state junior high school English teachers in Yogyakarta. This study involved 260 participants taken using cluster random sampling from the whole population of 790 state junior high school English teachers. Data were collected using a valid and reliable questionnaire. Afterward, the data were analyzed with descriptive statistics and the Kruskal Wallis test, along with a prerequisite of normality. This study revealed that the level of IC of state junior high school English teachers in Yogyakarta was high. Moreover, it has been found that their level of intercultural attitude (IA), intercultural skill (IS), and intercultural knowledge (IK) were categorized as high. In other words, these results indicate that the state junior high school English teachers in Yogyakarta have a capability to mingle with diverse people using a language effectively and appropriately. Importantly, this study showed that there were no significant differences in their IC level according to where they teach in four districts and one city. These mean that the locations where they teach do not affect their level of intercultural competence.